2015
DOI: 10.1016/j.ajog.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the host inflammatory response following implantation of prolapse mesh in rhesus macaque

Abstract: Objective To determine the predominant cell type (macrophage, T-lymphocyte, B-lymphocyte, mast cell) within the area of implantation of the prototypical polypropylene mesh, Gynemesh PS (Ethicon); and to determine the phenotypic profile (M1 pro-inflammatory, M2 anti-inflammatory) of the macrophage response to three different polypropylene meshes: Gynemesh PS (Ethicon), and two lower weight, higher porosity meshes, UltraPro (Ethicon) and Restorelle (Coloplast). Study Design Sacrocolpopexy was performed followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 35 publications
5
49
0
1
Order By: Relevance
“…However, we note that recent published studies have demonstrated that density of the mesh is a local driver of the host macrophage response, where increased local mesh density is associated with an increased local pro-inflammatory response [30, 31]. While investigation of the differences in the host response between fibers and knots was beyond the scope of the present study, it will be important to evaluate the effects of IL-4 coated mesh knots in order to illustrate the effects in the host response of the released IL-4 and the coating in the presence of high density and complex geometry of the implant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we note that recent published studies have demonstrated that density of the mesh is a local driver of the host macrophage response, where increased local mesh density is associated with an increased local pro-inflammatory response [30, 31]. While investigation of the differences in the host response between fibers and knots was beyond the scope of the present study, it will be important to evaluate the effects of IL-4 coated mesh knots in order to illustrate the effects in the host response of the released IL-4 and the coating in the presence of high density and complex geometry of the implant.…”
Section: Resultsmentioning
confidence: 99%
“…These materials have recently been shown to elicit a predominantly M1 type response which is associated with the potential for tissue degradation and downstream complications when unresolved [30, 31]. Macrophage modulation only in early-stages of the host response, but also localized to the tissue-implant interface was sought in the present study, representing an advantage over strategies promoting non-local and/or extended shifts in the host response as it limits the potential for adverse long-term interactions and exacerbation of conditions which may exist at distant sites.…”
Section: Introductionmentioning
confidence: 99%
“…Meshes with these characteristics have been shown to have less of a negative impact on the vagina in a primate model than their heavier weight, less porous counterparts. 2224 Second, all additional prolapse repairs performed in this trial will be native tissue further minimizing possible mesh-load and possible mesh-related complications…”
Section: Methodsmentioning
confidence: 99%
“…In a study conducted in Macacus rhesus, the post-implant inflammatory response to prolapse was characterized, elucidating the presence of proinflammatory cells after the PP mesh implantation [22]; in this study, the cellular immune response generated by the polypropylene mesh showed a predominance of proinflammatory cells type M1 macrophages within a few weeks of the surgical procedure; the researchers also found other proinflammatory cells to a lesser extent, such as CD45 (panleucocytes) that were distributed in the interstitium between the PP mesh and the host tissue, in addition to CD68-type macrophages that were widely distributed in each fiber of the mesh, while other cells were distributed in the periphery of its surface [22]. Several researchers have studied the post implantation effect with various polymeric materials, and have consistently observed the presence of inflammatory cells in polypropylene mesh tissue samples up to 8 years after their implantation; other researchers have observed the degradation of this material after implantation in humans [20].…”
Section: Discussionmentioning
confidence: 99%